2023
DOI: 10.1002/jee.20539
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning the future of learning and teaching engineering in the artificial intelligence era: Opportunities and challenges

Abstract: Generative artificial intelligence (AI) technologies, such as large language models (LLMs) and diffusion model image and video generators, can transform learning and teaching experiences by providing students and instructors with access to a vast amount of information and create innovative learning and teaching materials in a very efficient way (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This paper is funded by the teaching reform project of Zhujiang College of Tianjin University of Finance and Economics (ZJJG23-11Y), the key accounting research project of Tianjin Municipal Finance Bureau and Tianjin Accounting Society for 2023-2024 (Y230505), Humanities and Social Sciences Research Of the Ministry of Education(18YJA880064), the Tianjin statistical scientific research project, which is a deep study of Beijing-Tianjin-Hebei artificial intelligence industry in the context of "Ten Actions"(TJ2023KY02), and the Innovation and Practice of Collaborative AI Popularization Education Mechanism for New Liberal Arts, Politics, Industry, University, and Research (ZJJG21-07Z). 1…”
Section: Acknowledgementsmentioning
confidence: 99%
“…This paper is funded by the teaching reform project of Zhujiang College of Tianjin University of Finance and Economics (ZJJG23-11Y), the key accounting research project of Tianjin Municipal Finance Bureau and Tianjin Accounting Society for 2023-2024 (Y230505), Humanities and Social Sciences Research Of the Ministry of Education(18YJA880064), the Tianjin statistical scientific research project, which is a deep study of Beijing-Tianjin-Hebei artificial intelligence industry in the context of "Ten Actions"(TJ2023KY02), and the Innovation and Practice of Collaborative AI Popularization Education Mechanism for New Liberal Arts, Politics, Industry, University, and Research (ZJJG21-07Z). 1…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Sánchez-Ruiz, et al [106] examined the role of ChatGPT in the reinforcement of mathematical concepts. Qadir [4], Johri, et al [8], Berdanier and Alley [107] and Menekse [7] discussed areas of applications/concerns and encouraged engineering educators and policymakers to explore strategies for the ethical and efficient integration of AI tools across diverse aspects of the engineering education. Analyses by Carvallo and Erazo-Garzón [108] and Kwan [109] showed how ChatGPT can be employed as a micro-learning tool for Requirement Engineering and Engineering Statistics.…”
Section: Implications Of Genai Tools For Mechanical Engineeringmentioning
confidence: 99%
“…However, our understanding of the far-reaching pros and cons that this new chapter in digital competency portends across various domains is only just taking shape. To underscore this, a string of recent studies and commentaries in this area [3][4][5][6][7][8] have revealed how the discourse around GenAI risks has triggered policy measures to confront the hard question of what to do with these tools. Yet, while many of the prior studies have conveyed the menacing impact of GenAI tools on the education industry and various business sectors [9][10][11], this work is motivated by the fact that there are still some grey areas that demand further attention.…”
Section: Introductionmentioning
confidence: 99%
“…One significant area that stands to benefit from AI's transformative potential is Islamic Da'wah-the practice of inviting others to understand and embrace Islam (Saputra et al, 2024). As Da'wah traditionally relies on personal interaction and community engagement, integrating AI offers unprecedented opportunities to enhance its reach, effectiveness, and adaptability (Menekse, 2023). However, this integration also presents unique challenges that must be addressed to ensure the authenticity and ethical dissemination of Islamic teachings (Ibegbulam C.M et al, 2023).…”
Section: Introductionmentioning
confidence: 99%